Ensuring the Quality and Safety of Food Products as a Necessary Element of Public Health Protection and a Condition for Ensuring National Security of the Country - Elena V. VORONTSOVA; Andrey L. VORONTSOV (Communications of International Proceedings, 2020)
The article deals with the problematic issues of legal assurance of food quality and safety from the point of view of its significance for ensuring the right of citizens to health protection. The authors note that the quality and safety of food products and the legal mechanism for ensuring them is a necessary element of protecting the health of citizens and a condition for achieving food security in the country. Analyzing the regulatory framework in the field of food quality and safety, the authors conclude that it does not fully protect the interests of public health, and therefore does not adequately contribute to ensuring food and national security of the country. Among the shortcomings of the current legal mechanism for ensuring the quality and safety of food products, the authors highlight: the half-hearted nature of this mechanism (legal regulation focuses on ensuring product safety), the content uncertainty of the basic concepts («food quality», «food safety»), declarative provisions in the field of food quality assurance and the lack of clear quality criteria.
Keywords: right to health protection; quality and safety of food products; national security; health; legal assurance of quality and safety; legal regulation; food security; public health.